Screening for Plants Sensitive to Heavy Metals Using Cytotoxic and Genotoxic Biomarkers - Kwankua, Wimol; Sengsai, Supanyika; Muangphra , Pathumporn; Euawong, Nongnuch (Agriculture and Natural Resources, 2012)
Cytotoxic and genotoxic sensitivity to heavy metals were investigated in ﬁ ve plant species using a mitotic index (MI) and mitotic aberration (MA) as biomarkers. The results showed that Eucrosia bicolor and Allium cepa was more sensitive to cadmium toxicity at concentrations ranging from 0.02 to 0.09 mg.L-1 of CdCl2 than A. cepa var. ascolonicum, Zephyranthes rosea and Wedelia triloba. A decrease in the ‰MI and an increase in the ‰MA were found in E. bicolor as early as 24 hr after Cd treatment. Testing with lead (Pb), copper (Cu) and arsenic (As) showed that E. bicolor and A. cepa, to be sensitive to toxicity by Pb at the lowest dose of 0.2 mg.L-1 of Pb(NO3)2. Cyto-genotoxicity from Pb was also dose dependent. E. bicolor showed greater sensitivity than A. cepa in testing for Cu sensitivity. The lowest dose (1.00 mg.L-1) of CuCl2 caused a signiﬁ cant decrease in the ‰MI only in E. bicolor. The highest frequency of chromosome aberration type induced by Cu was different from that of Pb. E. bicolor was less sensitive to As cyto-genotoxicity compared with A. cepa. Only at 10.00 mg.L-1 of NaAsO2 could a signiﬁ cant decline in the ‰MI and an increase in the ‰MA be observed in E. bicolor, whereas the lowest dose which affected the ‰MI and the ‰MA of A. cepa was 0.25 mg.L-1. This is the ﬁ rst report which has studied and explored the potential of E. bicolor for use as a heavy metal cytotoxic and genotoxic bioindicator.